Diffractive Optics and Micro-Optics 2002
DOI: 10.1364/domo.2002.dtuc5
|View full text |Cite
|
Sign up to set email alerts
|

Micro-sized Fourier spectrometer

Abstract: We present a miniaturized Fourier transform spectrometer based on optical microelectro-mechanical system (OMEMS) technology. The spectrometer is a Michelson interferometer with one scanning mirror. An electrostatic comb drive actuator moves the mirror. The measured resolution of the spectrometer is 6 nm at a wavelength of 633 nm. In addition, we propose a method to integrate micro-optical components, like cylindrical lenses and beamsplitters, into the silicon chip with the actuated mirror.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…[1] There are some applications based on optical microsystems which are under investigation as microspectrometers, [2,3] confocal microscope for sample analysis, [4] optical coherence tomography (OCT) for in-vivo cancer detection, [5][6][7][8] and laser microsurgery. [9] It is observed that most optical microsystems are based on MEMS scanners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] There are some applications based on optical microsystems which are under investigation as microspectrometers, [2,3] confocal microscope for sample analysis, [4] optical coherence tomography (OCT) for in-vivo cancer detection, [5][6][7][8] and laser microsurgery. [9] It is observed that most optical microsystems are based on MEMS scanners.…”
Section: Introductionmentioning
confidence: 99%
“…In-plane displacement presented in Refs. [2,3,[10][11][12] for 1 DoF, and Refs. [4,13] for 2DoF (X-Y).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lower-resolution miniature spectrometers have become attractive because of new applications, expanding opportunities in a remarkable variety of disciplines and industries. 1 Miniaturization could make instruments and sensors easier to handle, faster, and cheaper. Such spectrometers have various applications, including color measurement, quality and process control, gas detection, and chemical analysis.…”
mentioning
confidence: 99%
“…The design concept and actuation principles are described in Ref. 1, and a diagram of the operation is shown in Ref. 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation